Speech act analysis of President Jalal Talabani’s address at the UN general assembly on September 25, 2008 - Ahmed, Hazhar; Mohammad, Othman Saleh; Arcelus, Juana; Amir, Shamaila; Mansoor, Ali (Linguistics and Culture Review, 2021)
Iraqi President Jalal Talabani addressed the United Nations General Assembly (henceforth UNGA) on September 25, 2008. In his address, he spoke about Iraqi legislative elections, long-term security concerns in the country and region, and called on the international community to authorize an international probe into attacks in Iraq which he said could not have been carried out without outside support. He said terrorist attacks that killed dozens of people, have reached the level of genocide and crimes against humanity. This paper aimed to highlight the speech acts used by President Jalal Talibani in this address using qualitative and quantitative methods of analysis. This paper also analyzed the direct and indirect speech acts employing the framework of Austin and Searle. The findings revealed that his address includes a balanced use of direct and indirect speech acts while maximum use of representative acts is evident. The paper concludes that the speech act analysis highlights the informative and supportive nature of President Talabani as he was able to highlight the problems of the country and at the same time ensuring every possible effort and support for the sake of raising the country to international community standards.